2021
DOI: 10.11606/s1518-8787.2021055003051
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal colostrum immunotherapy and nutrition in preterm newborns: meta-analysis

Abstract: OBJECTIVE To investigated the effect of oropharyngeal colostrum immunotherapy in reducing the time required for very low birth weight preterm newborns (VLBW-PTNB: < 1,500g and < 37 weeks) to achieve full enteral nutrition. METHODS Literature search was conducted using four databases, including gray literature, with additional manual search of the references of selected articles. Eligibility criteria consisted of randomized clinical trials, without restriction regarding the date or language of the publica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Only one study has reported neurodevelopment at 6 months of corrected gestational age. 22 Although several meta-analyses were published on the use of OPCA in the last few years, 10,[36][37][38][39][40][41][42] we updated this meta-analysis as several recently published studies 11,[13][14][15]27 were not included in these meta-analyses. In the two recent meta-analyses, 37,40 there was evidence for a reduction in NEC Stage 2 or 3 and any sepsis, but not for culture-proven sepsis and mortality, though there was a trend towards reduction in these two critical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study has reported neurodevelopment at 6 months of corrected gestational age. 22 Although several meta-analyses were published on the use of OPCA in the last few years, 10,[36][37][38][39][40][41][42] we updated this meta-analysis as several recently published studies 11,[13][14][15]27 were not included in these meta-analyses. In the two recent meta-analyses, 37,40 there was evidence for a reduction in NEC Stage 2 or 3 and any sepsis, but not for culture-proven sepsis and mortality, though there was a trend towards reduction in these two critical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Infants receiving colostrum reached full enteral feeding earlier, around 7.2 days, compared to 9.1 for the control group (p < 0.05) [ 28 ]. Numerous other studies have concluded that the effective full enteral feeding time was significantly reduced in pre-term infants receiving OAC compared to those in the control group [ 32 , 34 , 36 , 38 - 40 , 44 , 45 ]. Reaching full enteral nutrition sooner may improve the development of the digestive system of pre-term infants and reduces cytokine release.…”
Section: Reviewmentioning
confidence: 99%
“…Because of limited sample size and inconsistent OAC measures, among other reasons, there is no sufficient evidence to prove that OAC can reduce the incidence of NEC, LOS and death [ 40 ]. But OAC can promote intestinal maturation and rapidly achieve total enteral feeding [ 41 , 42 ]. However, the mechanism by which OAC promotes intestinal maturation by changing intestinal microbiota and metabolites remains elusive, which is the significant contribution of our study.…”
Section: Introductionmentioning
confidence: 99%